Between francophonie and world literature in French: Tahar Ben Jelloun's evolving authority. Issue 2 (14th March 2016) - Lewis, Mary Anne
ABSTRACT: One of the most prolific authors writing in French today, Moroccan born Tahar Ben Jelloun has built a rich and multi-layered career as a literary figure and public intellectual in France. He is an excellent figure to use as a case study when analysing the specificities and implications of categorising a particular author and their works within such frameworks as 'francophonie' or 'world literature in French.' In this paper, I examine the contemporary culture industry's shaping of the authorial identity of Tahar Ben Jelloun, whether as writer or public persona. Specifically, this article considers Ben Jelloun at three particular moments in his career, and examines two fictionalised testimonials, Cette aveuglante absence de lumière (This Blinding Absence of Light) and Par le feu (By Fire) . Each of the three moments represents a particular positioning of the author's identity as, alternatively, Arab, Middle Eastern, francophone, African, some combination of these, or as a figure of World literature in French. The two texts were chosen because, despite their similarities in terms of genre and theme, stylistic differences between the two suggest that Ben Jelloun considered shaped the second with critiques of the first in mind. The positioning of Ben Jelloun at each of these junctures – whether by himself, his critics, his readers, or some combination of these – has profound implications for the way his work is read and for readers' understanding of the role of the author more generally.